Information literacy in selected public and private secondary schools in Quezon City exploring school library and media specialists' roles through the lens of connectivism theory - Santos, Patrick Gabriel B. (School of Library and Information Studies, University of the Philippines Diliman, 2015)
Since Information Literacy (IL) is globally considered as an essential skill for life-long learning and has recently been considered as a basic human right in the modern information society, a closer analysis on how it is being taught to students of nine selected secondary high schools in Quezon City, students in their early formative years; must be made. (Ramon Magsaysay (Cubao) High School, Quirino High School, Balara High School, Krus na Ligas High School, Quezon City High School, Ateneo de Manila High School, Miriam College High School, Diliman Preparatory School, and Claret School of Quezon City.) In light of this, an emerging paradigm, Connectivism Learning Theory was used to study the IL programs, schemes, and agenda that the schools offer and how as Information Professionals, School Library and Media Specialists' play their roles in assuring that students become information literate.